How small and medium-sized family enterprises in the tourism sector develop inter-organisational relationships: a case study - Hanna Łobejko (Studia Periegetica, 2022)
The purpose of this article is to identify factors influencing the way small and medium-sized family enterprises in the tourism sector form and maintain inter-organisational cooperation and evaluate their importance. The study is based on qualitative data collected during 19 standardised in-depth interviews with representatives of family businesses operating in the Podhale region, one of Poland’s major mountain destinations. The study’s conceptual framework is based on Christine Oliver’s determinants of relationship formation, which affect the way businesses establish inter-entity cooperation and achieve extended social embeddedness. Factors identified by the author include resource disparity, reciprocity, efficiency, stability, and formal elements. The study contributes to the literature on inter-organisational relationships by providing insights about the determinants of inter-entity cooperation in the SME sector and the functioning of family firms in Poland.